A Novel Strategy toward High‐Performance Lithium Storage of Li4Ti5O12 Using Cu2V2O7 as Additive. Issue 3 (6th January 2022) - Xu, Ningning; Zhao, Dexing; Wang, Rui; Han, Qing; Miao, Yongxia; Yang, Xinli; Xie, Lingling; Zhang, Caili; Zhu, Limin; Cao, Xiaoyu
Abstract : Cu2 V2 O7 is an important material to improve low conductivity of Li4 Ti5 O12 . Herein, Li4 Ti5 O12 /Cu2 V2 O7 with different Cu2 V2 O7 ratios is successfully prepared by a liquid phase‐assisted dispersion method. The results show that the electrochemical properties of Li4 Ti5 O12 are affected by the Cu2 V2 O7 content incorporated in the composites. Among all obtained samples, Li4 Ti5 O12 /0.05 Cu2 V2 O7 reveals the best electrochemical performance and capacity retention rate, and its first cycle specific capacity is 246.3/197.2 mAh g −1 when the current density is 30 mA g −1 and it maintains values of 175.8/175 mAh g −1 for 200 cycles between 1.0 and 3.0 V. The resulting Li4 Ti5 O12 /0.05 Cu2 V2 O7 composite also displays higher capacities at elevated current densities of 120 and 1200 mA g −1, with values always superior to those of the original Li4 Ti5 O12 . The detailed electrode dynamics analysis illustrates that the introduced Cu2 V2 O7 phase in the composites improves the cycle stability and lithium‐ion transfer rate of Li4 Ti5 O12 . Through in situ X‐ray diffractometry (XRD) test analysis of the Li4 Ti5 O12 /0.05 Cu2 V2 O7 composite material, it is confirmed that the lithium storage mechanism is improved, where metallic Cu is formed in situ during each charge and discharge reaction process; thereby, the electronic conductivity of the composite material is improved and charge transfer resistance of the bulk material is reduced. Abstract : Herein, Cu2 V2 O7 is used as an additive to boost the electrochemical performance of Li4 Ti5 O12 . Expectedly, the Li4 Ti5 O12 /0.05 Cu2 V2 O7 composites demonstrate high cycle capacity and high rate capability. In situ X‐ray diffractometry analysis verifies the enhanced lithium storage mechanism of Li4 Ti5 O12 /0.05 Cu2 V2 O7 composites due to in situ formation of metallic Cu during discharge/charge processes, which greatly improves the electronic conductivity of Li4 Ti5 O12 .